2010
DOI: 10.1007/s10530-010-9702-2
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of large- and small-scale disturbances on exotic tree invasion in a native tussock grassland relict

Abstract: It is generally accepted that disturbances increase community invasibility. Yet the role of disturbance in plant invasions may be less predictable than often assumed, due to the influence of environmental stochasticity and interactions between disturbance regimes. We evaluated the single and interactive effects of prescribed burning (large-scale, infrequent event) and animal diggings (small-scale, frequent events) on the invasion success of Gleditsia triacanthos L. in a tussock grassland relict of the Inland P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 50 publications
1
43
2
1
Order By: Relevance
“…These fi ndings show that different biotic factors may contribute to repel invasion by this native tree in both grasslands. In contrast, we found that even undisturbed grasslands were not fully immune to invasion by G. triacanthos (Mazía et al 2001(Mazía et al , 2010Chaneton et al 2004 ) .…”
Section: Inland Pampa: Tree Species Invasion In Old Fieldscontrasting
confidence: 68%
See 4 more Smart Citations
“…These fi ndings show that different biotic factors may contribute to repel invasion by this native tree in both grasslands. In contrast, we found that even undisturbed grasslands were not fully immune to invasion by G. triacanthos (Mazía et al 2001(Mazía et al , 2010Chaneton et al 2004 ) .…”
Section: Inland Pampa: Tree Species Invasion In Old Fieldscontrasting
confidence: 68%
“…5.6 ). Large-and small-scale disturbances thus promoted tree recruitment in the old fi eld, whereas they exerted antagonistic effects in the relict tussock community (Mazía et al 2010 ) . Final establishment of G. triacanthos was twice as high in the old fi eld as in the tussock grassland (Fig.…”
Section: Inland Pampa: Tree Species Invasion In Old Fieldsmentioning
confidence: 98%
See 3 more Smart Citations